Introduction To Traditional Sports Among Generation Z - Wali, Carles Nyoman; Selan, David R. E.; Kaho, Uly J. Riwu; Waluwandja, Petrisia Anas; Jado, Gregorius G.; Atto, Aplonia (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2024)
Traditional sports are one of Indonesia's treasures that were born from community games and have been preserved to this day. The aim of this community service is to introduce and provide descriptions of traditional sports, especially traditional sports of East Nusa Tenggara among generation Z. The method of service is practice and mentoring. Community service activities were carried out at Pasir Panjang Beach, Kupang City, East Nusa Tenggara. The implementation of service activities with the title introduction of traditional sports among generation Z was attended by 48 generation Z people with different educational backgrounds, knowledge, ages and playing abilities. Details 1). 39 people from high school and 8 from middle school. The service results show that knowledge about traditional sports is very low. This is based on the service results of 48 students, only 3 of whom knew quite well while 45 people did not know at all during the pretest. Then we carried out an introduction followed by a posttest which proved that there were significant changes, only 2 people still experienced problems playing. In this way, the service concludes that traditional sports must be carried out continuously and in stages to maintain the existence of traditional sports among generation Z. Generation Z really hopes that these activities will be carried out in the field of education, especially sports carrying out activities related to traditional sports